PENYELESAIAN PERKARA PIDANA ANAK YANG BELUM BERUMUR 12 (DUA BELAS) TAHUN PADA TINGKAT PENYIDIKAN DI POLRESTA PADANG - Suryadinata LBN Gaol; Elwi Danil; Aria Zurnetti (LPPM Universitas Ekasakti Padang, 2023)
Investigators, social counselors and professional social workers must work together and coordinate with each other so that the stages as stipulated in Government Regulation No. 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Children Who Are Not Yet 12 Years Old, the initial initiative for implementing this government regulation in The investigator's hand is supported by the role of social counselors and professional social workers in making decisions whether the perpetrators of children who are not yet 12 years old are returned to their parents/guardians or put in LPKS. The type of research used in this study is an empirical juridical approach and is descriptive analysis in nature. The roles of Investigators, Community Counselors and Professional Social Workers have their respective roles in coordinating the decision making of perpetrators of children under the age of 12 as stipulated in Government Regulation No. 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Underage Children 12 years old. the initial initiative for implementing these government regulations lies in the hands of investigators supported by the role of social counselors and professional social workers in making decisions whether the perpetrators of children who are not yet 12 years old are returned to their parents/guardians or admitted to LPKS.